Pokemon DP. Galactic battles : the complete season [videorecording (DVD)]
As the menace of Team Galactic continues to loom over the Sinnoh region, Ash and Dawn keep getting caught up in the schemes of this mysterious group of villains, as well as facing some other unexpected challenges! Dawn's got her hands full dealing with the many problems of her Pokemon, while Ash's ongoing rivalry with Paul finally comes to a head in a full six-on-six battle! It might be the ultimate test of training styles, will they come out on top?